Chemoselective Methionine Labelling of Recombinant Trastuzumab Shows High In Vitro and In Vivo Tumour Targeting. Issue 11 (18th January 2023) - Hashad, Rania A.; Jap, Edwina; Casey, Joanne L.; Candace Ho, Y. T.; Wright, Alexander; Thalmann, Claudia; Sleeman, Mark; Lupton, David W.; Hagemeyer, Christoph E.; Cryle, Max J.; Robert, Remy; Alt, Karen
Abstract: A highly effective 2‐step system for site‐specific antibody modification and conjugation of the monoclonal antibody Herceptin (commercially available under Trastuzumab) in a cysteine‐independent manner was used to generate labelled antibodies for in vivo imaging. The first step contains redox‐activated chemical tagging (ReACT) of thioethers via engineered methionine residues to introduce specific alkyne moieties, thereby offering a novel easy way to fundamentally change the process of antibody bioconjugation. The second step involves modification of the introduced alkyne via azide‐alkyne cycloaddition ′click′ conjugation. The versatility of this 2‐step approach is demonstrated here by the selective incorporation of a fluorescent dye but can also be applied to a wide variety of different conjugation partners depending on the desired application in a facile manner. Methionine‐modified antibodies were characterised in vitro, and the diagnostic potential of the most promising variant was further analysed in an in vivo xenograft animal model using a fluorescence imaging modality. This study demonstrates how methionine‐mediated antibody conjugation offers an orthogonal and versatile route to the generation of tailored antibody conjugates with in vivo applicability. Abstract : Schematic illustration of α‐HER2M IgG modification in a 2‐step approach using a redox‐activated chemical tagging and an azide–alkyne cycloaddition reaction.